Infographics as visualization for data management and sustainable development - Yensebaev, Тимур; Yuldasheva, Надира (Рroblems of engineering and professional education, 2023)
This article describes how to use geographic information system for the management of the city.Data visualization for easy reading of incoming information about the status of the city.